STUDENTS’ ENGAGEMENT OF AUDIO PODCAST-BASED LISTENING SKILL IN SENIOR HIGH SCHOOL - Putri Purwo Anggraini; Muhammad Reza Pahlevi; Abdul Kodir Al-Baekani (PROJECT (Professional Journal of English Education), 2023)
Due to the development of information and communication technology, various methods of teaching and learning English have developed. One of the cutting-edge resources that instructors use to improve language proficiency and promote classroom learning is podcasting. Language skills have always been the most difficult thing for foreign language students to learn in terms of student engagement and study subjects. In this study, the authors conducted research on student engagement in listening skills based on audio podcasts. The participants were 3 students from a senior high school in Karawang. This study used a qualitative descriptive method, aiming to obtain complete data and a comprehensive picture. Data collection techniques are interviews and observation. The result of this study is how students engage in listening skills based on audio podcasts. The active participation of a student in a learning activity is called engagement. Students are cognitively engaged when there are students who want to make their own podcasts at home to hone their skills in listening learning. Students are involved behaviorally, student involvement here is the physical involvement of students in listening skills. And lastly, students' affective or emotional involvement describes the social and emotional relationships of students with their learning activities. All students Although students can learn independently, they still need teacher guidance in learning to listen. Keywords:  Audio Podcast; Engagement; Listening Skill